Leveraging technological innovation, social media, and green marketing for corporate reputation: the mediating role of business sustainability - Jalal Rajeh Hanaysha; Khaled M.K. Alhyasat (Cogent Business & Management, 2025)
The primary aim of this paper was to investigate the impact of technological innovation, green marketing, and social media usage on corporate reputation. It also intended to verify if business sustainability really mediates the relationship among them. A self-administered survey was utilized for gathering the data from several owners and managers of several SMEs in the UAE. All responses were quantitatively analyzed via SmartPLS software. The analysis showed that technological innovation, social media usage and green marketing positively affect corporate reputation. Furthermore, the outcomes displayed that business sustainability fully mediates the link between the aforementioned constructs and corporate reputation. This research carries significant implications to the decision makers in SMEs for understanding the importance of the selected factors in building corporate reputation and enhancing their sustainable performance. The findings can also be considered by marketing practitioners for devising strategies aimed at nurturing the sustainability and reputation of their enterprises.